The Relationship between Parents Attention and Student Motivation in Class V Elementary School: Hubungan Perhatian Orang Tua Terhadap Motivasi Belajar Siswa Kelas V SD - Putri Dwi Maulida; Machful Indra Kurniawan (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to determine whether or not there is an influence of parental attention on the learning motivation of fifth grade students at an elementary school. The research method used in this research is descriptive quantitative research method. The instrument used for data collection is the parental attention questionnaire instrument and the learning motivation questionnaire in the form of a google form. Based on the results of calculations, From the results of the questionnaire and student scores, it can be concluded that there is a relationship between parents' attention to student learning motivation, this is evidenced by the results of the correlation test with the results of r arithmetic getting 0.472 while r table getting 0.344 so that the interpretation of the correlation test is r count (0.472 ) > from r table(0,344). So with this Ho is rejected and Ha is accepted and Sig.2-tailed <0.05 so it can be concluded that there is indeed a significant relationship between parental attention and learning motivation.